2001
DOI: 10.1111/j.1752-1688.2001.tb05528.x
|View full text |Cite
|
Sign up to set email alerts
|

SAMPLING FRAME FOR IMPROVING PEBBLE COUNT ACCURACY IN COARSE GRAVEL‐BED STREAMS1

Abstract: Improved sampling techniques are needed to increase the accuracy of pebble‐count particle‐size distributions used for stream studies in gravel‐bed streams. However, pebble counts are prone to operator errors introduced through subjective particle selection, serial correlation, and inaccurate particle‐size measurements. Errors in particle‐size measurements can be minimized by using a gravel template. Operator influence on particle selection can be minimized by using a sampling frame, 60 by 60 cm, in which sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
100
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 69 publications
(102 citation statements)
references
References 22 publications
(36 reference statements)
2
100
0
Order By: Relevance
“…However, when data were plotted, the ratio of the same percentile particle-sizes between heel-to-toe samples and sampling along a tape showed a systematic decrease with bedmaterial particle size (Fig. 4.5) (Bunte and Abt 2001). On fine gravel beds, heel-to-toe samples had coarser D 16 , D 50 and D 84 particle sizes than sampling along a tape.…”
Section: Statistical Detectability Of Operator Biasmentioning
confidence: 93%
See 2 more Smart Citations
“…However, when data were plotted, the ratio of the same percentile particle-sizes between heel-to-toe samples and sampling along a tape showed a systematic decrease with bedmaterial particle size (Fig. 4.5) (Bunte and Abt 2001). On fine gravel beds, heel-to-toe samples had coarser D 16 , D 50 and D 84 particle sizes than sampling along a tape.…”
Section: Statistical Detectability Of Operator Biasmentioning
confidence: 93%
“…Physical shape of the operator can also play a role in the variability of sampling results between operators in heel-to-toe pebble counts. Bunte and Abt (2001) compared sampling results obtained from heel-to-toe walks in a cobble-bed stream (D 50 = 69 mm, D max > 720 mm, sorting coefficient s I = 1.7 φ) between two operators of different size. The operator with a small boot size (Operator B) was more prone to avoiding cobbles and boulders, and produced particle-size distributions with fewer coarse particles than the operator with a large boot size (Fig.…”
Section: Operators Avoid Stepping Onto Cobbles and Bouldersmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that using a standard frame with fixed dimensions to assist gravel sampling reduces user-biased selections of gravels (Marcus et al, 1995;Bunte and Abt, 2001a). In order to reduce this bias, we substituted the frame by shooting an equal number of photos at a fixed distance (ca.…”
Section: Site Selection and Methodsmentioning
confidence: 99%
“…Therefore it is important to reduce bias by using a sampling grid [Bunte and Abt, 2001a;Marcus et al, 1995]. A grid was placed on the stream bed along transects, and diameters of particles beneath the grid intersections were measured with a template in half y units (y = log 2 (D pass )).…”
Section: Channel and Substrate Measurementsmentioning
confidence: 99%